Democracy and income inequality : an empirical analysis - Grâdšṭayn, Marq 1992- (Policy research working paper, 2001)
Ideology, as proxied by a country's dominant religion, seems to be related to inequality. In Judeo-Christian societies increased democratization appears to lower inequality; in Muslim and Confucian societies it has an insignificant effect. One reason for this difference may be that Muslim and Confucian societies rely on informal transfers to reach the desired level of inequality, while Judeo-Christian societies, where family ties are weaker, use political action